Outpatient treatment in uncomplicated acute diverticulitis: 5-year experience - Moya, Pedro; Bellon, Marta; Arroyo, Antonio; Galindo, Isabel; Candela, Fernando; Lacueva, Javier; Calpena, Rafael (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Most cases of diverticular inflammation are mild and require only medical treatment with liquid diet and antibiotics. Until recently, this treatment required admission to hospitals, which consequently entailed costs. In most cases, treatment was conservative, and less than a quarter of patients admitted actually underwent surgery. In the last year, the outpatient treatment of these patients with uncomplicated diverticulitis has proven effective and safe. The aim of the present study was to describe our experience after 5 years of outpatient treatment with oral antibiotics. Materials and Methods: We conducted a retrospective revision study between January 2010 and December 2014. We included all patients admitted to the Emergency Department of the University General Hospital of Elche with a diagnosis of uncomplicated acute diverticulitis based on medical history, physical examination and abdominopelvic computed tomography (CT) scanning. Outpatient treatment consisted of oral antibiotics for 10 days (metronidazole 500 mg/8 h and ciprofloxacin 500 mg/12 h), a liquid diet and oral analgesics (acetaminophen 1 g/6 h). Results: During the period from January 2010 to December 2014, 224 patients were treated on an outpatient basis at a success rate of over 92%. Only 18 patients (8%) required admission after outpatient treatment. Conclusion: Outpatient treatment of uncomplicated acute diverticulitis was demonstrated to be safe and effective.